2021
DOI: 10.31703/gmcr.2021(vi-i).18
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Usage and Mental Health: A Cross-Sectional Study in Pakistan

Abstract: Excessive social media usage can be harmful to the mental health of individuals. The core objective of the study was to inspect the effects of social media usage on mental health. Secondly, to find out the mean differences of gender, social media and mental health. A cross-sectional research design was utilized to fulfil the study objectives. n=1067 students from six different universities in Punjab, Pakistan, were selected through a multi-stage sampling technique. Data was collected through an adapted questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this study, a discourse analysis of tweets in the context of demand for public hanging of rapists is presented. Studies, such as Qadeer (2016), Kugelman (2012), and Pahore et al (2021) have shown that in the last few years a significant rise has been observed in the use of social media in Pakistan. It has become popular in use among people of all ages, using it through laptops, desktops, mobile phones, iPad, and tablets frequently.…”
Section: A Theory Of Discoursementioning
confidence: 99%
“…In this study, a discourse analysis of tweets in the context of demand for public hanging of rapists is presented. Studies, such as Qadeer (2016), Kugelman (2012), and Pahore et al (2021) have shown that in the last few years a significant rise has been observed in the use of social media in Pakistan. It has become popular in use among people of all ages, using it through laptops, desktops, mobile phones, iPad, and tablets frequently.…”
Section: A Theory Of Discoursementioning
confidence: 99%